Analisis Kesesuaian Lahan Untuk Tempat Pembuangan Akhir (Tpa) Sampah Di Distri Ransiki Kabupaten Manokwari Selatan - Wailola, Kermil; Alzair, Nur; Maurizka Mayzarah, Erikha (Jurnal Sains Geografi, 2025)
Ransiki District is one of the areas that has complex geological conditions and is very interesting to study. The Ransiki Fault is an active fault and is one of the main factors determining the suitability of land for a waste landfill based on geological aspects. The population growth in Ransiki District, South Manokwari Regency reached 16,245 people in 2020. However, until now there has been no landfill to accommodate waste from the community. Based on this, a land suitability study is needed to determine the location of a suitable waste disposal site. The data analysis method used in this study uses SNI No. 03-3241-1994. The results of this study, namely the regional stage which is overlaid from several parameters, produce 4 candidate locations for final waste disposal sites with candidate location 1 in Hamawi Village with an area of ​​136.51 Ha, candidate location 2 in Tobou Village with an area of ​​239.69 Ha, candidate location 3 in Sabri Village with an area of ​​413.12 Ha. Candidate location 4 is located in Kampung Sabri with an area of ​​101.45 Ha. The results of the preliminary stage from the weighting of each parameter where location 1 has a value of 495, location 2 has a value of 534, location 3 has a value of 543 and location 4 has a value of 483. From the results of the preliminary stage, the recommended location is location 3 which is located in Kampung Sabri, Ransiki District with the highest value of 543.